2016
DOI: 10.1016/j.jacc.2015.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Long-Chain Acylcarnitines in Heart Failure and Reversibility With Mechanical Circulatory Support

Abstract: Objectives Heart failure (HF) is characterized by perturbations in energy homeostasis and metabolism. The reversibility and prognostic value of circulating markers reporting on these changes remain unclear. We sought to describe the metabolomic profiles of patients along the spectrum of systolic HF, determine their association with adverse outcomes in a clinical trial of HF, and evaluate whether identified metabolites change with treatment for end-stage systolic HF. Methods To assess association of metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
132
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(154 citation statements)
references
References 32 publications
19
132
0
3
Order By: Relevance
“…Despite taking a very different statistical approach, two factors of our PMP (Arg, C18.1 AC) were also contributing factors in the most predictive principle component identified from the Ahmad study. (18) This consistency of our findings with those of previous investigators strongly supports external validity. (7,18,2629) Moreover, although the primary aim here was to validate the importance of circulating metabolites in HF and not define a biomarker, the PMP did statistically add to current optimal prognosticators; a high hurdle that few markers (such as troponin and neutral endopeptidase) have achieved (30,31)…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite taking a very different statistical approach, two factors of our PMP (Arg, C18.1 AC) were also contributing factors in the most predictive principle component identified from the Ahmad study. (18) This consistency of our findings with those of previous investigators strongly supports external validity. (7,18,2629) Moreover, although the primary aim here was to validate the importance of circulating metabolites in HF and not define a biomarker, the PMP did statistically add to current optimal prognosticators; a high hurdle that few markers (such as troponin and neutral endopeptidase) have achieved (30,31)…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, there is growing data derived from the setting of HF, in which specific plasma metabolite levels were reported to be associated with incident disease or risk of death (1115). More recently, a few systematic evaluations of the metabolites in HF were published which further support the overall hypothesis that circulating metabolites may be deranged in the setting of HF and indeed may reflect the underlying disease state (1618). Larger scale validation of the plasma metabolome regarding prognostic value, or as way to stratify HF phenotypes, is still urgently needed.…”
Section: Introductionmentioning
confidence: 80%
“…Similarly, our group recently found that patients with end‐stage HF had significantly higher plasma LCAC levels than those with chronic, stable HFrEF 51. Furthermore, we demonstrated that greater plasma LCAC levels were independently associated with worse functional status and mortality in chronic stable HFrEF 51. Altogether, the plasma LCAC elevations in HFpEF and HFrEF observed in our study and previous investigations may highlight a shared metabolic impairment characteristic of the HF state.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, they also found that Stage A HF patients had plasma LCAC levels higher than normal controls, but lower than Stage C HF patients. Similarly, our group recently found that patients with end‐stage HF had significantly higher plasma LCAC levels than those with chronic, stable HFrEF 51. Furthermore, we demonstrated that greater plasma LCAC levels were independently associated with worse functional status and mortality in chronic stable HFrEF 51.…”
Section: Discussionsupporting
confidence: 79%
“…21 Circulating levels of long-chain acylcarnitines are also increased in patients with end-stage HF compared with those who have chronic HF with systolic cardiac dysfunction, and this increase predicts the risk of hospitalization or death. 22 Interestingly, in contrast to the increased level of circulating acylcarnitine, acylcarnitines are reported to be reduced in the failing heart itself, possibly caused by increased utilization, altered carnitine metabolism, or decreased acylcarnitine synthesis. 23, 24 Phospholipids are molecules that generally have 2 hydrophobic fatty acid tails and a hydrophilic head, and form the major component of cell membranes.…”
Section: Metabolites Of Glycolysis and The Tca Cyclementioning
confidence: 99%